The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s12262-022-03348-w
|View full text |Cite
|
Sign up to set email alerts
|

Voice Disorders after Total Thyroidectomy: Prospective Evaluation by Patient Self-Assessment, Indirect Laryngoscopy and Ultrasonography

Abstract: Voice alterations after thyroidectomy with mobile vocal folds are common. Ultrasonography has been used to assess the mobility of the vocal folds after thyroidectomy. Fifty-four patients underwent thyroidectomy. Indirect laryngoscopy, ultrasonography, and GRBAS (grade, roughness, breathiness, asthenia, strain) scoring were performed preoperatively, 3 days, 2 and 6 months, postoperatively. On the third postoperative day, the mobility of the vocal folds was preserved in 52 patients and pareses were recorded in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Therefore, the VFI is anticipated to be a more delicate voice evaluation tool, especially in the context of thyroidectomy-related vocal fatigue. Most studies on voice impairment following thyroidectomy have demonstrated an elevation in the GRBAS scale postsurgery, and this increase is frequently proportional to the subjective evaluations provided by patients [ 2 , 17 , 21 ]. However, no significant change was observed in the GRBAS scale for patients in a study related to post-thyroidectomy [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the VFI is anticipated to be a more delicate voice evaluation tool, especially in the context of thyroidectomy-related vocal fatigue. Most studies on voice impairment following thyroidectomy have demonstrated an elevation in the GRBAS scale postsurgery, and this increase is frequently proportional to the subjective evaluations provided by patients [ 2 , 17 , 21 ]. However, no significant change was observed in the GRBAS scale for patients in a study related to post-thyroidectomy [ 22 ].…”
Section: Discussionmentioning
confidence: 99%